Research report appraisal: how much understanding is enough? - Lipscomb, Martin (Nursing philosophy, 2014)
When appraising research papers, how much understanding is enough? More specifically, in deciding whether research results can inform practice, do appraisers need to substantively understand how findings are derived or is it sufficient simply to grasp that suitable analytic techniques were chosen and used by researchers? The degree or depth of understanding that research appraisers need to attain before findings can legitimately/sensibly inform practice is underexplored. In this paper it is argued that, where knowledge/justified beliefs derived from research evidence prompt actions that materially affect patient care, appraisers have an epistemic duty to demand high (maximal) rather than low (minimal) levels of understanding regards finding derivation (i.e. appraisers have a duty to seek a superior epistemic situation). If this argument holds assumptions about appraiser competence/ability and the feasibility of current UK conceptions of evidence based practice are destabilized.